Exploring the roles of self-actualization, language self-efficacy, and academic emotions in EMI students’ achievement: a structural equation modeling approach - Guan, Yuan; Du, Lili; Yang, Chao; Hu, Hui-Ling (Frontiers in Education, 2025)
IntroductionStudents in English Medium Instruction (EMI) environments encounter unique challenges, including the simultaneous demands of language acquisition and academic achievement. This study explores how psychological factors –specifically self-actualization, language self-efficacy, internal locus of control, and learning anxiety –affect academic performance among Chinese university students enrolled in EMI programs.MethodsData were collected through 480 valid questionnaires completed by students from diverse academic disciplines. A structural equation modeling (SEM) approach was utilized to examine both the direct and indirect effects of self-actualization and language self-efficacy on academic achievement, with internal locus of control and learning anxiety as mediating variables.ResultsThe findings indicate that self-actualization significantly enhances internal locus of control, which in turn positively affects academic achievement. Although self-actualization also reduces learning anxiety, its indirect effect on academic performance via this pathway is comparatively weaker. Language self-efficacy was found to both reduce learning anxiety and directly improve academic achievement. Among the mediators, internal locus of control exerted the most substantial influence, highlighting its role as a key psychological determinant of academic success.DiscussionThis study contributes to the theoretical understanding of psychological and emotional variables in EMI contexts. The findings underscore the importance of fostering internal locus of control, managing learning anxiety, and enhancing language self-efficacy to support academic achievement. Practical implications include targeted interventions and support strategies to help EMI students navigate their dual learning demands more effectively.